Potential and Ecotourism Development in The Wee Boro Lake, Tebara Village, West Sumba District: Potensi dan Pengembangan Ekowisata di Kawasan Danau Wee Boro, Desa Tebara, Kabupaten Sumba Barat - Yus Sudarsono Muslim; Gatot Yulianto (Habitus Aquatica, 2025)
Wee Boro Lake is located in Tebara Village, West Sumba Regency. Wee Boro Lake was widely promoted as a tourist attraction on May 31 2023 and was attended by the regent of West Sumba, all village heads in West Sumba Regency, as well as other important stakeholders. Wee Boro Lake is located at the coordinates (°39'54" South Latitude and 119°25'13" East Longitude). This research aims to find out the level of suitability of tourism at Lake Wee Boro. The analysis used in this research is SWOT analysis as a method for developing conditions and evaluating a problem based on internal factors (Strength and Weakness) and external factors (Opportunity and Threats). The research results show that the appropriate ecotourism activity to carry out at Lake Wee Boro is boating. Sitting and camping activities are only suitable to be carried out at station 1. Fishing activities are not or are not yet suitable to be carried out at Wee Boro Lake. Camping, boating, fishing and relaxing tourism activities respectively have a carrying capacity of 176 people/day, 636 people/day, 8 people/day and 40 people/day.